Influence of Turn-Taking in Musical and Spoken Activities on Empathy and Self-Esteem of Socially Vulnerable Young Teenagers - Hawkins, Sarah; Farrant, Camilla (Frontiers in Psychology, 2022)
This study describes a preliminary test of the hypothesis that, when people engage in musical and linguistic activities designed to enhance the interactive, turn-taking properties of typical conversation, they benefit in ways that enhance empathy and self-esteem, relative to people who experience activities that are similar except that synchronous action is emphasized, with no interactional turn-taking. Twenty-two 12-14 year olds identified as socially vulnerable (e.g. for anxiety) received six enjoyable 1-hour sessions of musical improvisation, language games that developed sensitivity to linguistic rhythm and melody, and cross-over activities like rap. The Turntaking group (n=11), practiced characteristics of conversation in language games, and these were also introduced into musical activities. This involved much turn-taking and predicting what others would do. A matched control group, the Synchrony group, did similar activities but in synchrony, with less prediction and no turn-taking. Task complexity increased over the six sessions. Psychometric testing before and after the series showed that the Turntaking group increased in empathy on self-report (Toronto Empathy Questionnaire) and behavioral (‘Reading the Mind in the Eyes’) measures, and in the General subtest of the Culture-Free Self-Esteem Inventory. While more work is needed to confirm the conclusions for relevant demographic groups, the current results point to the social value of musical and linguistic activities that mimic entrained, tightly-coordinated parameters of everyday conversational interaction, in which, at any one time, individuals act as equal participants who have different roles.